Back in My Day: A Journal Club Using Landmark Articles for Emergency Medicine-Bound Medical Students - San Miguel, Christopher E. (West J Emerg Med, 2020)
This journal club style curriculum was developed to advance 4th year medical students in Emergency Medicine (EM) Milestone 19. The curriculum was introduced as part of a longitudinal boot camp course for EM- bound students. Students met monthly with faculty members to critically evaluate landmark articles within the field of EM. The curriculum culminated with student group presentations of two contemporary research articles with opposing conclusions. Discussed articles covered the following topics: stroke care, head trauma, cervical spine trauma, pulmonary embolism, cardiology treatments, syncope, post- cardiac arrest care, pediatrics, sepsis, and fluid resuscitation. The curriculum was evaluated using the institution’s standard student educational session evaluation form. Students rated the quality of the sessions highly, and based on thematic review of comments, the journal club was a beneficial addition to the boot camp curriculum.